Metode Pemahaman Islam Muḥammad Al-Ghazāli (Kajian Analisis Kitab Kaifa Nafham Al-Islām) - Munawir Darwis (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2019)
The Style of Islamic understanding has a correlation with the progress and welfare of its people. Methodological error to interpret Islam will be trapped in the stagnation of thought and decline of the people. Therefore, one of the efforts of the reformers of Islam was to reconstruct the methodology as an important tool in understanding Islam to be able to provide a solution to the problems of humanity and sovereignty. This research attempts to reveal how the approach used by Muhammad al-Ghazāli in understanding Islam, the background of his Islamic Thought and its advantages and disadvantages. Based on the result of the study, al-Ghazāli’s thought was influenced by educational background at Al-Azhar and social-political conditions in Egypt. One of the efforts made by al-Ghazāli was to call for a total return to the Islamic manhaj (way) completely as the only way to overcome the religious and social problems of Muslims.This concept methodologically is an effort to understand Islamic values ​​through the approach of the Qur'an and Sunnah which is interpreted through the spirit of rationality in the frame of moderation. Based on this approach Islam is not only understood as a doctrine but also a solutions to humanitarian and muslim problems.